Studi Komparasi Model Pembelajaran Kooperatif Think Pair Square dengan Model Pembelajaran Kooperatif Student Teams Achievement Divisions terhadap Hasil Belajar Fisika - Sriwahyuninsi Sriwahyuninsi; Amiruddin Hatibe; Kamaluddin Kamaluddin (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine the differences in physics learning outcomes between classes using the Think Pair Square cooperative learning model and the Cooperative Student Teams Achievement Divisions. The research method used is a quasi-experimental, with a research design "the non equivalent pretest-posttest design". The sample was selected using purposive sampling technique. The research sample was class VIII G as experimental class A (32) and class VIII F as experimental class B (34). The instrument used was a multiple-choice test of learning outcomes. Based on the results of data processing, for the experimental class A the mean score of the initial test was 7.81 and the final test score was 20.06. In the experimental class B, the mean score of the initial test was 8.68 and the final test score was 18.79. The results of statistical calculations from hypothesis testing using the t-test concluded that there are differences in physics learning outcomes between classes that follow the Think Pair Square learning model and Student Teams Achievement Divisions at SMP Negeri 3 Palu.